High-pressure synthesis and magnetic properties of tetragonal R2BaCuO5 (R = Sm and Eu) - Mishra, Swarnamayee; Yanda, Premakumar; Bhat, Shrikant; Etter, Martin; Sundaresan, A. (Frontiers in Chemistry, 2023)
We report the experimental discovery of a new structural phase of well-known orthorhombic R2BaCuO5 (R = Sm and Eu), exhibiting a tetragonal crystal structure with space group P4∕mbm. The high-pressure tetragonal phase is isostructural with the brown phase R2BaCuO5 (R = La, Pr, and Nd). In this structure, the Cu ions form an isolated square planar environment, contrary to the orthorhombic phase, where the Cu ions are located in a distorted square pyramid. Magnetization and specific heat measurements reveal the long-range antiferromagnetic order of the Cu2+ and/or Sm3+ moments for the Sm-sample, with the magnetic specific heat accounting for only 35% of the magnetic entropy. Interestingly, the Eu-sample remains paramagnetic down to the lowest temperature. The high Curie-Weiss temperature of −140 K and magnetic entropy of 3% of the expected value indicates that the system is highly frustrated. We estimated the isothermal entropy change and investigated the magnetocaloric effect for Eu2BaCuO5, and the maximum entropy change detected at a field of 70 kOe at 3 K reaches 5.6 J kg-1K−1.